Moderate Islamic Education: A Comparative Study of Indonesia’s Insan Cendekia and Turkey’s Imam Hatip Schools - Abdul Hadi; Sarbini Anim; Hadi Yasin; Sutiono Sutiono (Research Synergy Foundation, 2025)
The idea of a